ANALISIS MODEL SIR-ASI PADA PENYAKIT DEMAM BERDARAH DENGUE - Anjel Agustina; Pardi Affandi (MAp (Mathematics and Applications) Journal, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus infection through the bite of the Aedes Aegypti mosquito. The high number of cases of DBD from year to year has become a major health problem in Indonesia. DBD can be modeled using mathematical modeling to understand the dynamics of disease spread through the stability of the equilibrium point and optimal control of the problem of DBD transmission. The DBD model is classified into 2 types of classes: the human population class and the mosquito class. There are three subclasses for the human population class: the susceptible population, the infected population, and the recovered population. Meanwhile, the mosquito population class is divided into three subclasses, namely the aquatic population, the susceptible population, and the infected population. The aims of this study were to determine a mathematical model for the spread of Dengue Hemorrhagic Fever, to reconstruct the model, to determine the optimal control form for DBD, and to perform numerical simulations. The result of this study is the formation of the SIR-ASI model for DBD. Based on this model, two equilibrium points are obtained, namely a disease-free equilibrium point and an endemic equilibrium point. Then the basic reproduction number (R_0 ) is obtained through the Next Generation Matrix method.